KOSTRUKSI SOSIAL MASYARAKAT TELUK MERANTI KABUPATEN PELALAWAN PROVINSI RIAU ATAS REALITAS BONO - Bulmei Always; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Bono is a unique natural phenomenon that occurs in the Kampar River Pelalawan Riau Province. Bono is a natural phenomenon that comes before the tide. Bono waves have a great potential to be one of the tourist destinations, now waves Bono has attracted the interest of local and foreign tourists through the process of externalizing society is the product of individuals who are objective realities and vice versa through a process of internalization of the individual is the product of people who become subjective reality. The purpose of this study is; Knowing the Teluk Meranti community Externalization Process About Reality Bono. Knowing the process of objectivation Society for Teluk Meranti About Reality Bono. Internalization Process To Know About Reality Society of Teluk Meranti Bono.This research is classified in descriptive qualitative research with phenomenological approach. This research was conducted in the village of TelukMerantiTelukMerantiPelalawan, Riau Province. Informants are people who are expected to assist authors in menggungkap actual reality in communities examined. Interview data collection techniques and observation.Results of this study explain that externalizing the village of TelukMeranti community is inseparable from the role of the electronic media and print media. but by making waves bono become a tourist attraction by the government Pelalawan submitted to various mass Mendia both electronic and print, so the outside world knows that the natural phenomenon bono waves make the sport pencitasurving or surfers come to try surfing in the waves bono. Objectivation bono waves in the village of TelukMeranti not independent of Government policy that makes waves Pelalawan bono become a tourist icon Pelalawan to build various infrastructures supporters to tourists easy access to attractions. Internalization villagers of TelukMeranti through visits of tourists who come to the village of TelukMeranti both local and foreign countries will lead to the internalisation among tourists and local communities, and the process of integration can be through exchange of culture, science, and so on which will be mutually affecting both sides.Keywords; Construction of Social, Community, Reality Bono.